Improvement of polyurethane foam growth behavior of within an aluminum mold with a comparison between a specialized software and applied tests. (2022) - Cabrera, Victor Hugo; Sandoval, Pablo; Silva, Maria; Juiña, Luis; Valdez, Marco
Abstract: The research carries out the simulation of the growth of the polyurethane foam inside a mold, in order to optimize the resources. The aim finds the accurate option within a production process both in the incorporation of a new product as in improving an existing one. Using the Moldex3D program, the project obtains a mathematical model to calculate parameters such as the viscosity of the material, pressure, volume, temperature, curing, foaming, heat capacity, thermal conductivity and mechanical properties of the material. The density obtained for the material analyzed experimentally is 59.09 kg·m −3 with a uniform watering at the base with a 10 degrees mold inclination with 1740 g of material and air outlets that help to obtain better conditions of mold, seeking to reduce the time used by 25% and reduce manufacturing costs.